Makna Simbol dalam Tradisi Burdahan di Pondok Pesantren Kramat - Madliyah nur lintang utami Lintang (Fakultas Ilmu Budaya, Universitas Jambi, 2020)
AbstractKramat Islamic Boarding School is one of the Islamic boarding schools that has a tradition of burdah prayer which is usually held on Thursday evenings Friday at eight o'clock, and the evening prayers. In the tradition of burial prayer there are things that have symbolic meaning. This study aims to determine the meaning of the symbols of the objects used in the activities of the body. This research is a library research because part of the research process utilizes various kinds of literature that are relevant to the problem under study. The data collection method uses the interview method. This research uses theoretical triangulation techniques. The data collected was analyzed by content analysis. Burdahan tradition is an activity that aims as an expression of longing and deep love for the Prophet Muhammad with all its implications. This burdah shalawat uses symbols that are used as decorative ornaments such as yellow mushrooms, ivory coconut, various fruits, various flowers that have meaning and contain advice that is so important for human life. Especially proposed for the congregation shalawat burdah. Keywords: the meaning of symbols and traditions